O protagonismo do anti-herói na obra de José Louzeiro: análise do processo de criação do roteiro do filme Pixote - A Lei do Mais Fraco - CASTELO BRANCO, Bruna Maria Paixão (2020)
This paper investigates the processes of socially marginalized character creation in the movie Pixote – A Lei do Mais Fraco, directed by Hector Babenco. The movie is inspired by the book Infância dos Mortos, written by José Louzeiro, that took part in the script writing. The creation process also included Hector Babenco and Jorge Duran.The study is inserted in a methodological field of research on genetic criticism. The goal is to understand the different treatments of the script, considering notes, drafts and information exchange among the writers. These elements help to identify the stages of development of main characters. Considering the historical context of Brazil at the time the movie was released, the research is divided into steps, in order to show elements that influenced the approaches of social themes. An overview of José Louzeiro’s work is outlined and the work also explains how the literary genre novel-news story was important to influence the cinema productions at that time. In order to understand the scenario, the work mentions authors such as Reimão (2011), Costa (2005) and Süssekind (1984), beyond the contextualization of the historical period of the time, as well as its influence on the production and freedom of expression in the field of arts. For a specific analysis of cinema, authors such as Gomes (1980), Xavier (1993) and Amancio (2007) are mentioned. Considering creation, there’s a connection to researches by Salles, who approaches the creation as a network building process. Finally, this work also approaches the directions to the book adaptation from the script analysis, focusing the socially marginalized character creation. It’s an unpublished analysis and the proposal is to contribute to the processes of creation.